Optical properties of Si nanowires: Dependence on substrate crystallographic orientation and light polarization. Issue 6 (13th March 2015) - Badán, Juan A.; Marotti, Ricardo E.; Dalchiele, Enrique A.; Ariosa, Daniel; Martín, Francisco; Leinen, Dietmar; Ochoa, Efrain; Ramos-Barrado, José R.
Abstract: Abstract : Optical properties of Si nanowire (SiNW) arrays prepared on p-doped Si(111) and Si(100) substrates were studied. SiNWs were synthesized by self-assembly electroless metal deposition nanoelectrochemistry in an ionic silver HF solution through selective etching. Total reflectance ( R t ) and total diffuse reflectance ( R dt ) of SiNWs change drastically in comparison to polished Si. To understand these changes, diffuse reflectance ( R d ) with polarized incident light was studied. For samples prepared on Si(111), the wave length integrated R d (wIRd) shows maxima at certain angles of incidence θ, regardless of the incident light polarization. For samples prepared on Si(100), wIRd increases with θ and depends on incident light polarization. Also, R d spectra show structures due to interference effects. Therefore, SiNWs prepared on Si(100) can be considered as thin films whose refractive index depends on light polarization. Moreover, R dt of SiNWs prepared on Si(111) can be modeled as an ensemble of diffuse reflectors.